Analısıs Kebutuhan Handout Bagı Mahasıswa MBKM Untuk Mata Kulıah Statıstık Pendıdıkan SD - Selvi Wulandari; Pamuti; Anwar Marasabesy; Santi M.J. Wahid (Jurnal Elementaria Edukasia, 2024)
This research aims to determine the extent to which students taking part in the MBKM program need handouts for educational statistics course material. This type of research is qualitative descriptive research. The research subjects were 30 PGSD students in semester V and semester VII. The results of the comprehension test showed that of the 13 Course Learning Outcomes (CPMK), only 3 CPMK were understood by MBKM students well with results of more than 60%, namely basics of statistics (83.33%), data presentation (67%) and measurement. central symptoms (67%). Interview analysis, of the 5 Graduate Learning Outcomes (CPL) that must be met, almost every CPL student experiences difficulties in realizing the CPL in the MBKM activities they participate in. Based on the results of comprehension tests and interviews conducted, MBKM students need handouts as a companion in carrying out activities. It is hoped that students can use this handout to understand the material independently and continue to follow MBKM activities well.